Respostas

2014-05-28T23:07:04-03:00
-x² + 6x - 5 = 0
a = -1
b = 6
c = -5
      Δ = b² - 4ac
      Δ = 6² - 4 . (-1) . (-5)
      Δ = 36 - 20
      Δ = 16
               x =  - b ± √Δ
                          2a
               x =  - 6 ± √16
                        2 . (-1)
               x' =  - 6 + 4 =  -2  ⇒ 1
                          -2        -2 
               x'' =  - 6 - 4  =  -10  ⇒ 5
                          -2          -2

As raízes da equação são 1 e 5.

Espero ter ajudado. Valeu!
7 4 7